ENHANCING ACTIVE LEARNING THROUGH KAHOOT IN CLASSROOM LESSONS - Zokirova Farzona Farruxjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Active learning has increasingly become a cornerstone of modern pedagogy, emphasizing the role of student engagement and participation in the learning process. This article explores the use of Kahoot, a game-based learning platform, as an effective tool to foster active learning in classroom lessons. Through a comprehensive analysis of pedagogical theories and practical applications, the study demonstrates how integrating Kahoot can improve student motivation, participation, knowledge retention, and formative assessment outcomes. Particular attention is given to the dynamics of instant feedback, collaborative competition, and learner autonomy facilitated by Kahoot.